Difficulties in the collection of data and information in Romania - Elisabeta Haba; Sabina Popescu; Victor Velter (Annals of Spiru Haret University Economic Series, 2011)
The purpose of this paper is to highlight the difficulties encountered by any person or company when searching for valuable information on the official sites of the ministries or state institutions, using the available search keys. At the same time, the paper states the necessity to design a new, comprehensive database, with another two keys (one primary and one secondary), in order to better assist the search effort. The data and information contained in this database should be accurate, supplied in a timely manner and against small or no fees. At the same time, the level of the information supplied as result of the search should strictly observe the present regulation regarding the privacy of data and information in the European Union.